An Analysis of The Relationship Between Digital-Based Financial Report Transparency and Willingness to Pay (WTP) For Environmental Fees in The Post-Pandemic Era - Neti Erlina; Muhamad Irfan Florid; Liestyowati; Hendra Kasman; Mohamad Yusuf Golam (Yayasan Inovasi Kemajuan Intelektual, 2025)
In the aftermath of the global pandemic, public trust in institutional spending has become a critical determinant of civic participation in environmental sustainability. This study investigates the relationship between digital-based financial report transparency and the Willingness to Pay (WTP) for environmental fees among urban citizens. As digital transformation accelerates, the accessibility and clarity of financial disclosures serve as a bridge between governmental accountability and public contribution. Utilizing a quantitative approach, this research examines how real-time digital reporting mitigates perceived corruption and enhances the perceived value of environmental protection initiatives. The findings suggest that transparency does not merely fulfill a legal obligation but acts as a psychological catalyst that significantly increases WTP. When citizens can verify that their contributions are allocated efficiently through digital platforms, their resistance to additional environmental levies decreases. This research provides a framework for policymakers to leverage digital accounting tools as a strategy for sustainable environmental financing in the post-pandemic era.